NePodmazhesh - NePoedesh: Lexical Representation of Bribery Topic in Russian Languge - A. V. Shchetinina (Научный диалог)
The problem of description of the social vocabulary functioning in different linguistic strata in certain historical periods is considered on the example of the lexical representations of the topic of bribery in the Russian language. The relevance of the study is determined by the lack of a comprehensive description of the vocabulary of social interaction, including institutional relations, the scope of which includes bribery. It is shown that in the vocabulary of the Russian language this topic is represented by words, idioms and non-idiomatic expressions, as well as proverbs that reflect the perceptions of Russian native speakers of one of the parts of social interaction of citizens and government members. 312 linguistic facts, containing semes ‘bribery’, which are included in the structure of the meanings of the words that constitute the lexical-semantic field “Bribery” are identified. Ideographic net is developed, which determines the structure and composition of the field. It is noted that the semantic field center is the ideogram “the custom of taking bribes”; its key lexical represent is the noun bribery . The idea about this phenomenon as about custom is stated. Interpretive analysis of the contexts in which you use this concept is made. Based on the analysis it is concluded that proverbs objectify semantic components of the concept of custom: identifying, regulating, etc.